Harassed : gender, bodies, and ethnographic research - Hanson, Rebecca, 1983-; Richards, Patricia, 1971- (University of California Press, 2019)
"Researchers frequently experience sexualized interactions, sexual objectification, and harassment as they conduct fieldwork. Nevertheless, these experiences are often left out of ethnographers' "tales from the field" and remain unaddressed within qualitative literature. Harassed argues that the androcentric, racist, and colonialist epistemological foundations of ethnographic methodology contribute to silence surrounding sexual harassment and other forms of violence. The authors challenge readers to recognize how these attitudes put researchers at risk; furthers the solitude experienced by researchers; leads others to question the validity of their work; and, in turn, negatively impacts the construction of ethnographic knowledge. With the intent to improve methodological training, data collection, and knowledge produced by all researchers, Harassed advocates for an embodied approach to ethnography to reflexively engage with the ways that researchers' bodies shape the knowledge they produce. By challenging these assumptions, the authors offer an opportunity for researchers, advisors, and educators to consider the multiplicity of ways good ethnographic research can be conducted"--Provided by publisher.